Literature review on Prosopis africana and the use of essential oils as preservatives - GANGBE, Modesty; KPATINVOH, Brice; ATTREVY, Brice; ALLAGBE, Aymard; DEGNON, GNIMABOU RENÉ (My University, 2021)
Abstract: The present study aims to review the status of Prosopis africana, the fermentation of its seeds and the use of plant extracts (essential oils) as a preservative for foodstuffs. This study reveals that the main uses of Prosopis africana are human food, fodder, wood as a source of energy, production of handicrafts and furniture and traditional pharmacopoeia. It also shows that the seeds are fermented to produce food condiment (Okpeye) which is a rich food and promotes the development of certain microorganisms. In order to maintain the quality of foodstuffs, industrialists use chemical agents to preserve their food products causing huge health problems. Some recent studies show that the use of essential oils can be an alternative to preserve the quality of foodstuffs. This review of the literature therefore focuses on Prosopis africana and the use of essential oils as a preservative for foodstuffs.
Keywords: Prosopis africana; fermentation; essential oils; seeds.